Role of the Specialized Pro-resolving Mediator Resolvin D1 in Hashimotoʼs Thyroiditis - Song, Jing; Sun, Rongxin; Zhang, Yuanyuan; Fu, Ying; Zhao, Dong (Experimental and Clinical Endocrinology & Diabetes, 2021)
Objective Resolvins are produced by the catabolism of polyunsaturated fatty acids (PUFAs) and play vital roles in inflammation resolution. Resolvins have been associated with autoimmune disorders. This study aimed to measure the level of Resolvin D1 (RVD1) in the serum of Hashimoto's thyroiditis (HT) patients and healthy controls (HCs) and to further analyse its correlation with thyroid autoantibodies and inflammatory factors.Methods Sixty-three participants were recruited, namely, 30 untreated HT patients and 33 sex- and age-matched HCs. Serum RVD1 and inflammatory chemokine (MCP-1 and IP-10) levels were measured by ELISA according to the manufacturer’s protocol. Serum total T3 (TT3), TT4, free T3 (FT3), FT4, thyroglobulin antibody (TgAb), thyroid peroxidase antibody (TPOAb) and thyroid-stimulating hormone (TSH) levels were measured using an electrochemiluminescence immunoassay. Thyroid homeostasis parameters, including the thyroid secretory capacity (SPINA-GT), the total deiodinase activity (SPINA-GD), Jostel’s TSH index (TSHI) and the thyrotroph thyroid hormone sensitivity index (TTSI), were calculated.Results Serum RVD1 levels in HT patients (134.76, 85.35–201.36 pg/mL) were significantly lower than those in HCs (187.64, 131.01–326.85 pg/mL) (P=0.004). As the TPOAb level increased, the RVD1 level showed a decreasing trend (P for trend=0.002). Both multinomial and ordinal logistics analyses revealed that serum RVD1 levels were negatively correlated with TPOAb levels in the adjusted models. Moreover, RVD1 showed a negative correlation with the inflammatory chemokine IP-1 0 (r=–0.276, P=0.034), TSHI (r=–0.269, P=0.036) and TTSI (r=–0.277, P=0.031).Conclusions Thyroid autoimmunity may be associated with low levels of RVD1. Decreased RVD1 levels indicate impaired resolution of inflammation in HT patients.
Keywords: Hashimotoʼs thyroiditis; resolvins; serum; TPOAb; thyroid